Hubungan Stress Pembelajaran Daring Dengan Emotional Eating Pada Mahasiswa - liyanovitasari liyanovitasari (Indonesian Journal of Nursing Research (IJNR), 2022)
Online learning to be done only through homework remote assignments without feedback or interaction with students. In this way, if done continuously it can increase stress on students. If stress cannot be controlled, stress can affect emotional eating. To determine the correlation between stress in online learning and emotional eating among students at Ngudi Waluyo University. This type of research is descriptive correlational. The population is all Health Faculty students at Ngudi Waluyo Ungaran University with a population of 2452 students. The sample technique uses a proportional stratified random sampling method. The research sample was 96 respondents. The measuring instrument used was the PSS-10 (Perceived Stress Scale) and EADES (Eating and Appraisal Due to Emotions and Stress) questionnaire. Analysis using univariate and bivariate data (Spearman Rank correlation coefficient). As many as 82 (85.4%) students experienced moderate stress and as many as 94 (97.9%) students experienced high emotional eating. The correlation between stress and emotional eating in students of the Faculty of Health, Ngudi Waluyo University, from the results of statistical tests with rank spearman, got a p-value of 0,000 and the results of the Spearman correlation test obtained a value of 0.404 which indicates a moderate relationship between stress and emotional eating in to students of the Faculty of Health, Ngudi Waluyo University.